Herd-Level on-Farm Mortality in Extensively Managed Beef Herds. Issue 4 (1st October 2020) - Mõtus, Kerli; Niine, Tarmo; Viltrop, Arvo; Emanuelson, Ulf
ABSTRACT: The herd on-farm mortality rate is an indicator of herd animal health and welfare status. The aim of the present study was to describe herd-level on-farm mortality rates and to identify risk factors that contribute to high herd mortality rates. Online or postal questionnaires were sent to 676 Estonian beef farms, and the response rate was 25.4%. The calf (ear-tagged) and cow within-herd mortality rates for the years 2014–2016 ranged from 0.00 to 5.45 per 100 calf-months and 0.00–12.15 per 100 cow-years, respectively. The risk factors for a higher calf within-herd mortality rate in the negative binomial regression analysis were the following: calvings not being monitored at nighttime, bedding not being added daily, a low proportion of calvings occurring during summer, lack of using a consultancy service and conventional herd type compared to organic. Failure to separate sick animals and failure to use new pastures for cow-calf pairs were risk factors for cow mortality. Mortality rate was generally higher in larger herds. In order to lower the mortality rate, it is essential to ensure good calving management, a clean environment, and isolation of sick animals.